2016
DOI: 10.1111/bcpt.12654
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibitory Effects of Carbon Monoxide on Six Venoms Containing Fibrinogenolytic Metalloproteinases

Abstract: Since the introduction of antivenom administration over a century ago to treat venomous snake bite, it has been the most effective therapy for saving life and limb. However, this treatment is not always effective and not without potential life-threatening side effects. We tested a new paradigm to abrogate the plasmatic anticoagulant effects of fibrinogenolytic snake venom metalloproteinases (SVMP) by inhibiting these Zn -dependent enzymes directly with carbon monoxide (CO) exposure. Assessment of the fibrinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…The most effective treatment against coagulopathy in this setting still remains the administration of long-acting or multiple doses of antivenom as recently demonstrated [2]; however, coagulopathy can still occur and recur. Of interest, as a therapy complementary to antivenom, our laboratory discovered that direct, isolated exposure of snake venom metalloproteinases (SVMP) and snake venom serine proteases (SVSP) to carbon monoxide (CO) in vitro resulted in a marked decrease in associated fibrinogenolytic or thrombin-like activity in human plasma [3][4][5][6]. This observation was then extended into and confirmed in an in vitro whole-blood rabbit model wherein the SVMP fibrinogenolytic activity of Crotalus atrox venom was attenuated by pre-exposure to CO [7].…”
mentioning
confidence: 99%
“…The most effective treatment against coagulopathy in this setting still remains the administration of long-acting or multiple doses of antivenom as recently demonstrated [2]; however, coagulopathy can still occur and recur. Of interest, as a therapy complementary to antivenom, our laboratory discovered that direct, isolated exposure of snake venom metalloproteinases (SVMP) and snake venom serine proteases (SVSP) to carbon monoxide (CO) in vitro resulted in a marked decrease in associated fibrinogenolytic or thrombin-like activity in human plasma [3][4][5][6]. This observation was then extended into and confirmed in an in vitro whole-blood rabbit model wherein the SVMP fibrinogenolytic activity of Crotalus atrox venom was attenuated by pre-exposure to CO [7].…”
mentioning
confidence: 99%
“…With regard to the concentration of CatroxMP-II used, the onset of coagulation had to be double and/or the velocity of clot formation half of plasma without CatroxMP-II addition to be acceptable for experimentation. The following elastic modulus-based parameters previously described (Nielsen 2018; Nielsen and Bazzell 2016, 2017; Nielsen et al 2016, 2018a, b; Nielsen and Losada 2017; Nielsen and Matika 2017) were determined: time to maximum rate of thrombus generation (TMRTG): this is the time interval (minutes) observed prior to maximum speed of clot growth; maximum rate of thrombus generation (MRTG): this is the maximum velocity of clot growth observed (dynes/cm 2 /second); and total thrombus generation (TTG, dynes/cm 2 ), the final viscoelastic resistance observed after clot formation. Data were collected for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently demonstrated that the hemotoxic venom activity of several species of snakes can be inhibited in vitro and in vivo by exposure to carbon monoxide (CO) via thrombelastography (Nielsen 2018; Nielsen and Bazzell 2016, 2017; Nielsen et al 2016, 2018a, b; Nielsen and Losada 2017; Nielsen and Matika 2017). Also of interest, an agent that causes metheme formation (Nielsen et al 2011a) used to identify fibrinogen as a heme binding protein (Nielsen et al 2011b) was demonstrated to decrease the prothrombotic activity of Oxyuranus microlepidotus venom (Nielsen et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings of the clot strengthening effects of CO led us to hypothesize that CO may be able to strengthen clot formation in plasma from normal dogs exposed to Prairie rattlesnake ( Crotalus viridis) venom and in plasma from naturally envenomed dogs . To date, CORM‐2 has been shown to mitigate coagulopathy induced by several crotalid venoms in human plasma . Coagulopathy is a common sequel to rattlesnake bites in human beings and canine victims.…”
Section: Introductionmentioning
confidence: 99%